Statistical Optimization of Novel Medium to Maximize the Yield of Exopolysaccharide From Lacticaseibacillus rhamnosus ZFM216 and Its Immunomodulatory Activity - Chen, Liang; Gu, Qing; Zhou, Tao (Frontiers in Nutrition, 2022)
The traditional media used for the fermentation of Lactobacilli always contain carbohydrate polymers, which interfere the analysis of the exopolysaccharide (EPS) produced by the bacteria. In this investigation, a novel medium formulation which could avoid such interference was successfully developed. The beef extract, yeast extract and peptone used in this formulation were subjected to the removal of polysaccharide before use. The factors affecting the EPS production was optimized by single factor test, Plackett-Burman design and Box-Behnken design. The optimum formula was ascertained as: 7.5 g L-1 yeast extract, 12.5 g L-1 beef extract, 10 g L-1 peptone, 21.23 g L-1 maltose, 5.51 g L-1 yeast nitrogen base, 2 g L-1 K2HPO4, 5 g L-1 anhydrous sodium acetate, 2 g L-1 ammonium citrate, 0.58 g L-1 MgSO4·7H2O, 0.25 g L-1 MnSO4·H2O, 1 mL L-1 Tween 80. The initial pH of the medium was 6.5. The optimized conditions for fermentation of the strain to produce EPS were: seed size 1%, culture temperature 37 °C and culture time 20 h. Optimum results showed that EPS yield was 496.64±3.15 mg L-1, being 76.70% higher than that of unoptimized conditions (281.07±5.90 mg L-1). The EPS was mainly comprised of glucose and guluronic acid, with a weight average molecular weight of 19.9 kDa; it was also characterized by Fourier transform infrared spectroscopy and UV analysis. EPS was found to significantly enhance the phagocytic capacity, promote the NO, TNF-α, IL-1β, IL-6 secretion and improve mRNA expression of cytokines in RAW 264.7 macrophages, indicating its considerable immunomodulatory activity. Western bolt and immunofluorescence results demonstrated that the EPS was able to increase p65 nuclear translocation in the macrophages, indicating that EPS enhanced immunity via NF-κB signaling pathway. EPS investigated in this work has potential as an attractive functional food supplement candidate for hypo immunity population.